2020
DOI: 10.1523/jneurosci.1327-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex-Driven Dopamine Signals in the Striatum Show Unique Spatial and Pharmacological Properties

Abstract: Dopamine (DA) signals in the striatum are critical for a variety of vital processes, including motivation, motor learning, and reinforcement learning. Striatal DA signals can be evoked by direct activation of inputs from midbrain DA neurons (DANs) as well as cortical and thalamic inputs to the striatum. In this study, we show that in vivo optogenetic stimulation of prelimbic (PrL) and infralimbic (IL) cortical afferents to the striatum triggers an increase in extracellular DA concentration, which coincides wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…Moreover, the interactions between ChIs, cortico‐, thalamo‐, and nigro‐striatal afferents appear to be reciprocal (Fig. 1), 120‐124 further supporting the view that ChIs serve as an essential striatal integrator that orchestrates complex movements and error‐triggered corrections 125‐128 …”
Section: Attentional–motor Integration In the Striatum: Chis As Essenmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, the interactions between ChIs, cortico‐, thalamo‐, and nigro‐striatal afferents appear to be reciprocal (Fig. 1), 120‐124 further supporting the view that ChIs serve as an essential striatal integrator that orchestrates complex movements and error‐triggered corrections 125‐128 …”
Section: Attentional–motor Integration In the Striatum: Chis As Essenmentioning
confidence: 64%
“…119 Moreover, the interactions between ChIs, cortico-, thalamo-, and nigro-striatal afferents appear to be reciprocal ( Fig. 1), [120][121][122][123][124] further supporting the view that ChIs serve as an essential striatal integrator that orchestrates complex movements and errortriggered corrections. [125][126][127][128] A recent series of experiments were designed to test the general hypothesis that ChIs are essential attentional-motor integrators.…”
Section: Attentional-motor Integration In the Striatum: Chis As Essenmentioning
confidence: 64%
“…In agreement with previous findings ( Noble, 2003 ; Neville et al, 2004 ; Klein et al, 2007 ; Savitz et al, 2013 ), adult ankk1 27 ins/ 27ins mutant fish showed reduced expression of drd2 protein in the pallium and subpallium. The zebrafish subpallium corresponds to the striatum of mammals, which has been shown to be involved in processes such as motor learning ( Adrover et al, 2020 ). We also observed absence of drd2 protein in the hypothalamus of ankk1 27ins/27ins .…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicates that PFC can regulate attention and working memory by modulating memory-related activity within the PFC [ 45 47 ]. The striatum is richly innervated by midbrain DA neurons, which regulate a range of cellular and synaptic functions that control goal-directed behavior and habits [ 48 , 49 ]. The hippocampus serves a key function in memory, navigation, and cognition [ 50 ].…”
Section: Discussionmentioning
confidence: 99%